Analysing a discussion on an online university forum: A communicative approach to discursive democracy - Postma, L. (South African Journal of Higher Education, 2019)
This paper explores academics’ interaction in an online forum, where perceptions of racism are debated. The communicative model of democratic discourse directs the interpretation of an emancipatory discursive interaction, following a deductive textual analysis of the forum and interview texts from selected participants. The communicative model discourages normative judgements of others and focuses on an understanding of difference. The findings indicate that participants who engage in a deliberative demonstration of power, do not appreciate diverse social-historical contexts. Discursive interactions which indicate an understanding of participants’ contexts are marked by a mitigating and sympathetic approach which allows for doubt in the judgements of participants. These mitigating interactions do however not persuade all participants to critically reflect on limiting opinions, attitudes and ways of interaction. An online curator who invites participants from diverse contexts might make the discourse more nuanced, create the opportunity to understand multiple realities and facilitate a transformative discussion.